The intention to enroll among students of private higher learning institutions - Nazlan, Mohamed Nazidin; Ishak, Ismail; Hasnah, Haron (KnE Social Sciences, 2019)
Higher education hub in Malaysia has become intense in the form of competition. Private Higher Learning Institutions (HLIs) has to work harder to win the competition between the education services in the marketplace. Thus, with the total numbers of Private HLI and programmes available for choice, it is a complex situation to investigate the way students select Private HLI. Due to that, it is a key issue for Private HLI owners to understand what are the determinant factors that influence the students’ intention to enroll in Private HLI. This conceptual paper discusses the influence of promotional efforts, the role of family and attitude on the intention to enroll in private HLIs. Theory of Reason Action is used as the underpinning theory for this conceptual paper. The outcome of this study from the findings will be able to assist Ministry of Education and Private HLIs on how to increase the enrolment of Private HLIs and thus to assist them on how to meet the objective of the Malaysian Education Blueprint 2015-2025.